2021
DOI: 10.37871/jbres1364
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimers Disease-Like Neuropathology Following Exposure to Ambient Noise

Abstract: Many factors play a role in the risk of dementia, including the environment. Widespread and significant worldwide exposure to noise, the severity of related health consequences, and the limited tools available to the public to protect themselves strongly support the WHO's argument that 'noise pollution is not only an environmental nuisance but also a threat to public health'. Exposures to noise from industrial activities, airport noise, or occupational noise are very important. One of the limitations of such s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Behavioral and cognitive alteration by ethanol consumption in humans is replicated in animal rodent models [42].…”
Section: Neuroprotective Effects Of Thiazolidine-4-carboxylic Acid De...mentioning
confidence: 95%
“…Behavioral and cognitive alteration by ethanol consumption in humans is replicated in animal rodent models [42].…”
Section: Neuroprotective Effects Of Thiazolidine-4-carboxylic Acid De...mentioning
confidence: 95%
“…The WHO reported that exposure to air pollution is responsible for around 7 million deaths per year [1]. Exposure to air pollution has previously has been characterized to contribute to detrimental CNS occurrences such as neuroinfl ammation, neurodegeneration, and stroke [2][3][4]. While a variety of environmental factors are involved in neuronal infl ammation leading to CNS disease, air pollutants may be the most common source of environmental oxidative stress and infl ammation.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 is a severe respiratory infection, so particles from the breath and speech may contain the virus. Our previous fi ndings show that particulate matter and airborne particles reach the brain and aff ect the health of the Central Nervous System (CNS), and may cause various neuropsychological and pathological disorders [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. In addition, in line with global regulations, governments enacted public health regulations, including mandatory quarantine, social exclusion, and job quarantine, in an eff ort to limit the prevalence of COVID-19 [19].…”
Section: Introductionmentioning
confidence: 99%